Noise and vibration mitigation for rail transportation systems : Proceedings of the 10th International Workshop on RailwayNoise, Nagahama, Japan, 18-22 October 2010 - Maeda, Tatsuo (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2012)
This volume contains the contributions to the 10th International Workshop on Railway Noise, held October 18-22, 2010, in Nagahama, Japan, organized by the Railway Technical Research Institute (RTRI), Japan. With 11 sessions and 3 poster sessions, the workshop featured presentations by international leaders in the field of railway noise and vibration. All subjects relating to 1. prospects, legal regulation, and perception; 2. wheel and rail noise; 3. structure-borne noise and squeal noise; 4. ground-borne vibration; 5. aerodynamic noise and micro-pressure waves from tunnel portals; 6. interior noise and sound barriers; and 7. prediction, measurements, and monitoring are addressed here. This book is a useful "state-of-the-art" reference for scientists and engineers involved in solving environmental problems of railways.